Cryo–electron microscopy structures of human cone visual pigments - Qi Peng; Jian Li; Haihai Jiang; Xinyu Cheng; Probal Nag; Gunnar Kleinau; Trevor D. Lamb; Leon Busche; Qiuyuan Lu; Sili Zhou; Yidi Liu; Yuting Zhang; et al. (Science, 2026)
Human trichromatic color vision relies on three cone opsins [long-, middle-, and short-wavelength-sensitive opsins (LWS-, MWS-, and SWS-opsins, respectively)], whereas scotopic rod vision is mediated by rhodopsin. Although the structure of rhodopsin was solved more than 20 years ago, cone opsin structures have been lacking. Here, we present cryo–electron microscopy structures of the three human cone opsins, each bound to a G protein and all- trans retinal in the presumed active state. All three cone opsins differ markedly from rhodopsin. Within the retinal binding pocket, we identified a distinct counterion site (LWS- and MWS-opsins) and a ring of serines around the retinal (SWS-opsin). The active cone opsin structures explain how amino acid substitutions fine-tune spectral sensitivity and help clarify the molecular basis of color vision deficiencies and key differences in rod versus cone activation.